Analisis Distribusi Kecepatan Aliran Sungai Musi (Ruas Jembatan Ampera sampai dengan Pulau Kemaro) - Fathona Fajri Junaidi (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
River is the open channel that forms naturally on the surface of the Earth and does not only store water but also flows the water from upstream to downstream. Musi River serves as a transportÂ means, center of trades, industries, the source of clean water, drainage and flood control of Palembang. The activity on the river may be affected by the stream flow velocity distribution. In this study the velocity distribution analysis will be carried out in order to know flow velocity distribution on the surface as well as the discharge, how to determine the characteristics of flow. Then the stream flow velocity distribution was plotted by using the Surfer 11 program. The data from the field was processed and analyzed. The flow characteristics were then determined Â by using Froude Number and Reynolds Number. The result showed that flow was turbulent and subcritical. Â Key Words : open channel, flow velocity distribution, flow characteristics, surfer 11